Application and evaluation of Benefit Finding Scale (BFS) in early-stage cancer patients from China. (August 2016) - Liu, Zhunzhun; Gudenkauf, Lisa; Zhang, Lanfeng; Wang, Zunhui
Abstract: Purpose: To adapt the Benefit Finding Scale (BFS) from English to a Chinese version after considering cross-cultural influences, to validate the tool for assessing benefit in Chinese-speaking patients with early-stage cancer, and to analyze the relationships between BF and sociodemographic and disease-related variables. Methods: In part I of the study, the Chinese BFS was adapted from the English version by developing guidelines after due consideration for cross-cultural influences. The translation validity index was used for assessing the quality of translation, and further refining was carried out by administering the scale on early-stage cancer patients (N1 = 200, N2 = 351) in part II and III. The Chinese version of the BFS was analyzed for reliability, dimensionality and construct validity. Relationships between BF and sociodemographic and disease-related variables were analyzed by ANOVA and regression models. Results: The Chinese BFS was received favorably by patients during the preliminary testing. Cronbach's alpha and interclass correlation coefficients exceeded 0.7, and factor analysis yielded six factors. Convergent validity, discriminant validity and concurrent validity results indicated a satisfactory psychometric value. Sociodemographic and disease-related predictors of BF were observed. Conclusion: The Chinese BFS demonstrated good patient acceptability and exhibited strong psychometric properties among Chinese patients with early-stage cancer. There were differences between Chinese cancer patients' benefit finding and patients with cancer in foreign countries, domestic cancer patients revealed high score in social relationship and family relationship dimension. Educational level, monthly individual income, treatment and physical exercise were the predictors of Chinese cancer patients' benefit finding. Highlights: This study aims to cross-culturally adapt and validate a Chinese version of the BFS for patients with early-stage cancer. The paper provides a strict cross-cultural adaptation process and detailed cultural differences in understanding the BFS. This study could provide BFS additional evidence for the stability of its psychometric assessments across different cultures.